2019
DOI: 10.1111/rec.13072
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term effects on ecosystem services of quarry restoration with Technosols under Mediterranean conditions: 10‐year impacts on soil organic carbon and vegetation development

Abstract: The use of Technosols for the restoration of limestone quarries overcomes the usual “in situ” scarcity of soil and/or its poor quality. The use of mine spoils, improved with mineral and/or organic amendments, could be an efficient and environmentally friendly option. Properly treated sewage sludge from urban wastewater treatment plants could be a suitable organic amendment and fertilizer (rich in N and P) whenever its pollutant burden is low (heavy metals and/or organic pollutants). Its appropriate use could i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…As expected, this finding could be related to the higher rates of organic matter, TN, and TP in SS (Table 1). Similar results have been reported by Chen et al [69] and Carabassa et al [70], who observed that SS addition showed increases in the contents of SOC, TN, and TP, and thus positively improved the soil fertility. Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems.…”
Section: Responses Of Soil Properties To Ss Applicationsupporting
confidence: 90%
“…As expected, this finding could be related to the higher rates of organic matter, TN, and TP in SS (Table 1). Similar results have been reported by Chen et al [69] and Carabassa et al [70], who observed that SS addition showed increases in the contents of SOC, TN, and TP, and thus positively improved the soil fertility. Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems.…”
Section: Responses Of Soil Properties To Ss Applicationsupporting
confidence: 90%
“…Ten years of limestone quarry restoration under Mediterranean climatic conditions using municipal sewage sludge‐amended technosols boosted the vegetation cover to 80% with a higher frequency of ruderal species than 62% (control). Moreover, differences in N status were even greater with more than three times the N concentration in sludge‐amended technosols (1800 mg kg −1 ) compared with an un‐amended technosol extremely poor in N (500 mg kg −1 ) (Carabassa et al, 2019). The authors recommended moderate doses of organic amendment (sewage sludge) at 45 Mg ha −1 with technosols for maximum benefits and fast recovery of mine‐degraded lands.…”
Section: Reclamation Approachesmentioning
confidence: 99%
“…It is possible to preserve the newly formed topography as a secondary or replacement habitat for species, but these areas may become an ecological trap (Salguiero et al, 2020). To stabilise soil conditions, it is proposed to introduce engineering solutions for strengthening or constructing new artificial slopes (Wang et al, 2018), implementation of identification of water erosion processes by remote sensing (Padro et al, 2022) and filling with additional materials to protect groundwater (Semeraro et al, 2019), improvement of the organic component by sewage sludge (Carabassa et al, 2020) or carrying out transplanting of soil and plant litter from undisturbed areas (Benetkova et al, 2020). In the case of a slow succession, it is advisable to perform a biological stage of reclamation, provided that the ecological plant species inherent in the region are selected (Sampaio et al, 2021).…”
Section: I T E Rat U R E R E V I E Wmentioning
confidence: 99%